PERAN MANAJEMEN STRATEGI DALAM INOVASI PENDIDIKAN DI ERA DIGITALISASI PADA SDN SUNGAI HANYAR KECAMATAN BATUMANDI KABUPATEN BALANGAN - Hernani; Khuzaini; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2025)
This research focuses on the significance of quality-based strategic management in schools within the digital era, where educational institutions face various challenges and opportunities arising from technological advancements. The digital transformation in education necessitates schools to adopt more innovative approaches to educational management to enhance learning quality. The objective of this study is to analyze the challenges faced by schools in implementing quality-based strategic management and to explore how digital opportunities can be leveraged to improve educational effectiveness. The research method employed is a literature review, where the researcher collects and analyzes various sources of information from books, journals, and relevant articles. This process involves synthesizing data from existing literature to identify best practices and effective management models in digital education. The findings indicate that despite numerous challenges, such as a lack of resources and adequate training for teachers, there are significant opportunities to enhance educational quality through technology. This study finds that the implementation of responsive and adaptive strategic management can assist schools in confronting challenges and capitalizing on available opportunities. Recommendations for future educational practices include the development of a curriculum integrated with technology and the enhancement of collaboration among schools, parents, and the community.